Clinical Risk Factors for Extended Spectrum B-lactamase-producing Bacteriuria in Children with Myelodysplasia Performing Clean Intermittent Catheterization - ŞEKERCİ, ÇAĞRI AKIN; TARCAN, TUFAN; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2020)
Objective: To evaluate the clinical risk factors contributing to the development of extended spectrum beta-lactamase (ESBL)- producing asymptomatic bacteriuria in myelodysplastic children performing clean intermittent catheterization (CIC). Materials and Methods: The clinical risk factors for ESBL-producing bacteriuria were retrospectively investigated in 60 myelodysplastic children who had asymptomatic bacteriuria and were performing CIC. A total of 60 children were included in this study, 30 children (17 females, 13 males) with ESBL-positive bacteriuria in urine culture were identified as the study group and 30 age- and gender-matched ESBL-negative children (16 females, 14 males) served as controls. All children had neurogenic bladder due to myelodysplasia and had been used anticholinergics. The two groups were compared in terms of age, gender, presence of constipation and motor deficit, antibiotic prophylaxis, number of hospital admission, ultrasound findings, and presence of renal scarring in dimercapto succinic acid scintigraphy and urodynamic findings. Results: The mean age of the children was 77 +/- 50 months in study and 78 +/- 69 months in control groups. There was no statistically significant difference in terms of maximum bladder capacity, leak point pressure, constipation status and scarring. In study and control groups, 83% and 46% of children were on antimicrobial prophylaxis, respectively (p=0.007). Conclusion: ESBL-producing bacteriuria was found to be associated with long-term antibiotic prophylaxis. Thus, it was concluded that the use of antibiotics for asymptomatic bacteriuria should be kept to a minimum.
Keywords: Antibiotic prophylaxis; ESBL producing bacteriuria; Myelodysplasia; URINARY-TRACT-INFECTION; ESCHERICHIA-COLI; BETA-LACTAMASES; ANTIBIOTICS